Test problems for ordinary differential equations - Arushanian, O.B.; Zaljotkin, S.F.; Kalitkin, N.N. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2002)
A number of test problems for program performance evaluation in the field of ordinary differential equations (the case of Cauchy problem) are proposed. End-points of integration intervals and parameters of these tests may be varied to obtain more detailed information on properties of programs under study and on properties of the corresponding numerical methods.